Annual report 2016: Power of partnerships - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2017)
CCAFS annual report for 2016 describing regional highlights, publications, impact through policies and partnerships, capacity development and innovative communication, breakthrough science and innovation and integrating gender and youth, and so on.